Poststalinizm - Postavangardizm Das Subjekt und die Welt der Objekte in der postmodernen fruehen Lyrik Andrej Voznesenskijs - Dornblüth, Gesine (Slavistische Beitraege, 1999)
In examining the subject and his relation to the objects, it can be seen that Andrei Voznesensky's official poetry of the late 1950s and early 1960s contains postmodern elements; indeed, because it is unconsciously postmodern, it far exceeds the original conception of French philosophy from "postmodernism" corresponds to the so-called Russian Neoavantgarde. The aim of this work, to comprehensively and closely examine the relationship between subject and object in Voznesensky, and the comparative approach require that one limit oneself to exemplary analyzes. For this purpose, six poems were selected that are meaningful in relation to the subject.